Retinal sensitivity above macular neovascularization under anti-VEGF therapy in exudative neovascular age-related macular degeneration - Laurenz Pauleikhoff; Martin Ziegler; Isabel Bachmeier; Siqing Yu; Beatriz Garcia Armendariz; Daniel Pauleikhoff (BMC Ophthalmology)
Abstract Purpose Growth of macular neovascularization (MNV) associated with development of complete retinal pigment epithelial and outer retina atrophy (cRORA) been observed in eyes neovascular age-related macular degeneration (nAMD) under effective anti-vascular endothelial growth factor (VEGF) therapy. We aimed to evaluate the influence of the presence of MNV on the sensitivity of the overlaying retina both in patients with or without cRORA and to generate hypotheses about their association. Methods Pilot study on nAMD patients undergoing long-term anti-VEGF therapy that had also undergone microperimetry testing. Area of MNV and, if present, associated cRORA were identified on optical coherence tomography (OCT) volume scans and transposed onto en-face near-infrared images. Mesopic microperimetry performed at the same visit was then superimposed. Retinal sensitivity above the MNV and the surrounding retina were compared, excluding areas of cRORA. Results Twenty-six eyes (19 f, 7 m; age 79.3 ± 5.7 y; fu 4.0 ± 1.8 y; 7.4 ± 2.5 inj./y) were classified into a no cRORA (n = 11) and a cRORA group (n = 15). In the no cRORA group, mean retinal sensitivity above the MNV did not differ from the surrounding retina (20.9 ± 2.8 vs. 22.0 ± 2.4, p = 0.33), while in the cRORA group, a lower sensitivity above the MNV in comparison to the surrounding retina was observed (16.2 ± 3.4 vs. 19.9 ± 2.0, p = 0.001). Conclusion In the absence of cRORA, retinal sensitivity above the MNV did not differ significantly from that of the surrounding retina. These results could indicate a possible nutritional function of the MNV to the overlying retina in cases where no cRORA is present.